The Use of Give One Get One Strategy to Improve Students’ Reading Comprehension in Recount Texts - Zerra Novalina; Andini Septama Sari (Cipta Pustaka Nusantara, 2025)
Reading comprehension is a crucial skill in English language learning, yet many students struggle to understand texts effectively. This study investigates the effectiveness of the Give One, Get One strategy in improving students' reading comprehension. A quasi-experimental design was employed, involving 70 tenth-grade students from SMK Muhammadiyah Pagar Alam, divided into an experimental group (35 students) and a control group (35 students). Both groups took a pre-test before the treatment and a post-test afterward. The experimental group received instruction using the Give One, Get One strategy, while the control group followed conventional teaching methods. Statistical analyses, including paired sample t-tests and independent sample t-tests, revealed a significant improvement in the experimental group's reading comprehension scores. The findings indicate that the Give One, Get One strategy is an effective and engaging approach for enhancing reading skills, promoting active participation, and increasing students' confidence in reading English texts. Teachers are encouraged to adopt this strategy to foster a more interactive learning environment. Future research should explore its impact on other language skills, such as listening, speaking, and writing.